A collaborative model for representing wireless sensor networks' entities and properties - Brito, Lina M. Pestana Leão de (2022)
Wireless sensor nodes are, typically, resource limited. Therefore, the major functions of the Wireless Sensor Network (WSN) cannot be accomplished without collaboration among sensor nodes. In this paper, we present the Wireless Sensor Networks Supported Cooperative Work (WSNSCW) model. The key contribution of this model, when comparing to other models, is allowing for the representation of all the components and properties of a WSN. We also present the main entities and properties of this graph-based model, as well as its formalization.